2019
DOI: 10.1088/2515-7655/ab1ece
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of electrochemical hydrogen oxidation on different metal/ceramic model anodes and mechanistic implications

Abstract: Micro-patterned metal/ceramic model thin film electrodes were used to investigate the hydrogen oxidation mechanism on various metal/ion conductor combinations such as Ni/yttria-stabilized zirconia (YSZ), Pt/YSZ, Ni/scandia-stabilized zirconia, Ni/titania/YSZ. For all electrode types besides those with a continuous titania interlayer a triple phase boundary (TPB) and an area pathway could be separated. Moreover, activation energies as well as hydrogen and water reaction orders were determined for both pathways … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 36 publications
(21 reference statements)
0
8
0
Order By: Relevance
“…79−82 However, as of today, none has shown viability for application in fuel cells. 83,84 PGM-free HOR catalysts receive yet another blow when it comes to actual performance in fuel cells. Since low activity is a given, very high loadings are required to achieve reasonable performance.…”
Section: ■ Mechanism Of Her and Hormentioning
confidence: 99%
See 1 more Smart Citation
“…79−82 However, as of today, none has shown viability for application in fuel cells. 83,84 PGM-free HOR catalysts receive yet another blow when it comes to actual performance in fuel cells. Since low activity is a given, very high loadings are required to achieve reasonable performance.…”
Section: ■ Mechanism Of Her and Hormentioning
confidence: 99%
“…Both ceramic and macro-molecule groups have mostly exhibited relatively poor activity toward HOR, albeit improvement of noble and non-noble metals’ activity through synergistic effects has been observed and some have shown potential in theoretical studies. However, as of today, none has shown viability for application in fuel cells. , …”
Section: Pgm-free Catalysts For Hormentioning
confidence: 99%
“…The accuracy of the TPB calculation can be improved by another method. An interesting study by Doppler et al on Ni model electrodes with various TPB parameters as well as surface areas was reported 18,19 where they observed that the conductivity depended on the surface area when the TPB of Ni/YSZ was kept constant. This indicates that the reaction could occur not only through the TPB but also through the Ni surface.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous reports have described the resistance of Ni-YSZ to contain information related to the microstructure, particularly the TPB. [15][16][17][18][19][20] However, the correlation between electrode resistance and TPB length alone cannot provide information regarding microstructural changes. We believe that such correlations regarding the electrode capacitance, which is another parameter obtained by analyzing electrochemical impedance, must be derived.…”
mentioning
confidence: 99%
“…While research on nanostructured air electrodes has advanced, investigation of thin-film architectures for anode application remains a less explored field. State-of-the-art anode materials consist mainly of porous layers of metallic phases and metal-electrolyte composites. ,, Nevertheless, such structures present several limitations in terms of structural stability at high temperatures and sulfur poisoning . Moreover, their implementation in microdevices is hindered by the poor in-plane percolation of porous layers and by fabrication incompatibilities with typical thin-film deposition techniques.…”
Section: Introductionmentioning
confidence: 99%